Adventures in theoretical physics : selected papers with commentaries - Adler, Stephen L. (World Scientific series in 20th century physics, 2006)
"During the period 1964-1972, Stephen L. Adler wrote seminal papers on high energy neutrino processes, current algebras, soft pion theorems, sum rules, and perturbation theory anomalies that helped lay the foundations for our current standard model of elementary particle physics. These papers are reprinted here together with detailed historical commentaries describing how they evolved, their relation to other work in the field, and their connection to recent literature. Later important work by Dr. Adler on a wide range of topics in fundamental theory, phenomenology, and numerical methods, and their related historical background, is also covered in the commentaries and reprints." "This book will be a valuable resource for graduate students and researchers in the fields in which Dr. Adler has worked, and for historians of science studying physics in the final third of the twentieth century, a period in which an enduring synthesis was achieved."--Jacket